SISTEM INFORMASI LAYANAN JASA DAN PENJUALAN ATRIBUT SEKOLAH DENGAN METODE AGILE PADA USAHA MERAN JAYA PALEMBANG - Setiawan, Ichan; Sanmorino, Ahmad; Dhamayanti (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
Meran Jaya Palembang Enterprise is a business that provides services and sells school supplies, including uniforms and other items. Currently, all operations are conducted manually, resulting in numerous problems such as difficulties in tracking order status, stock recording errors, and low efficiency in generating sales reports. This research aims to design and implement a web-based information system using the Agile method. The system is designed to meet various needs, including customer data management, service ordering, and automatic and real-time sales processes. The Agile method was chosen for its ability to adapt to rapidly changing business requirements. The system was developed using PHP programming language and MySQL database for data storage, and tested using Blackbox Testing method to ensure its performance. Research findings indicate that this computer-based information system can improve operational management efficiency, reduce recording errors, accelerate transactions, and enhance customer service quality. With this system, it is expected that Meran Jaya Palembang Enterprise will become more competitive, organized, and responsive to customer needs in the digital era.